2010
DOI: 10.1016/s1470-2045(10)70146-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortality results from the Göteborg randomised population-based prostate-cancer screening trial

Abstract: Summary Background Prostate cancer is one of the leading causes of death from malignant disease among men in the Western world. One strategy to decrease the risk of dying from this disease is screening with Prostate-Specific Antigen (PSA); however, the extent of benefit and harm with such screening is under continuous debate. Methods In December 1994, 20 000 men born 1930 to 1944, randomly sampled from the Population Register, were computer randomised in a 1:1 ratio to a screening group invited for biennial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
639
0
34

Year Published

2011
2011
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 849 publications
(698 citation statements)
references
References 36 publications
14
639
0
34
Order By: Relevance
“…The United States-based Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial indicated that the death rate from prostate cancer was very low and did not differ significantly between a PSA screening group and a control group. 22 However, Hugosson et al 23 found that PSA-based population screening for prostate cancer led to a 44% reduction in prostate cancer disease-specific mortality. Higher contamination with opportunistic screening of the control group was thought to be the reason for the contradicting results of the US study.…”
Section: Prevalence Of Psa Screening In Men Over 50 Years Old Is Impementioning
confidence: 99%
“…The United States-based Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial indicated that the death rate from prostate cancer was very low and did not differ significantly between a PSA screening group and a control group. 22 However, Hugosson et al 23 found that PSA-based population screening for prostate cancer led to a 44% reduction in prostate cancer disease-specific mortality. Higher contamination with opportunistic screening of the control group was thought to be the reason for the contradicting results of the US study.…”
Section: Prevalence Of Psa Screening In Men Over 50 Years Old Is Impementioning
confidence: 99%
“…1 Initially, the role for hormonal treatment was restricted to men with metastatic and inoperable, locally advanced disease, but given the increase in prostate-specific antigen (PSA) testing, due to the recent PSA screening trials, [2][3][4] there has been a huge increase in the number of PCa cases detected. This earlier detection and downward stage migration has been accompanied by a proliferation of treatment alternatives, including its use as neoadjuvant or adjuvant therapy for surgery and radiotherapy, for biochemical relapse after surgery or radiation, and even as primary therapy for non-metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 Throughout the years, it became clear that the use of the PSA test in a screening setting has both advantages and disadvantages. The published results of the European Randomized study of Screening for Prostate Cancer (ERSPC), 5 the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial, 6 and the Gothenburg randomized population-based PC screening trial, 7 all initiated in the early 1990s, provide evidence on whether PSA testing is beneficial. The data from the three studies point towards a disease-specific mortality reduction due to screening, as well as the fact that screening by using a PSA test leads to overdiagnosis and therefore overtreatment.…”
Section: Introductionmentioning
confidence: 99%